2015
DOI: 10.5430/jnep.v5n9p17
|View full text |Cite
|
Sign up to set email alerts
|

The effect of guidance booklet on knowledge and attitudes of nurses regarding disaster preparedness at hospitals

Abstract: Background: Disasters have a potential of producing mass casualties thereby straining the health care systems. This means that hospitals need to be prepared for an unusual increase in workload, hence the importance of hospital disaster preparedness. Aim: The aim of the study to evaluate the effect of a guidance booklet on knowledge and attitude about disaster preparedness among nurses. Methods: Research design: A quasi experimental research design with pre-test post-test time series and follow up assessment. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 25 publications
(27 reference statements)
6
19
0
Order By: Relevance
“…Here, this study result shows a parallelism with other studies (Al Thobaity et al. ; Celik ; Diab & Mabrouk ; Li et al. ; Ozcan ; Wenji et al.…”
Section: Discussionsupporting
confidence: 92%
“…Here, this study result shows a parallelism with other studies (Al Thobaity et al. ; Celik ; Diab & Mabrouk ; Li et al. ; Ozcan ; Wenji et al.…”
Section: Discussionsupporting
confidence: 92%
“…Nurses' average score was also found moderate in the studies by Oztekin (2016) in Japan, and Chi Tzeng (2016) in Taiwan [19,20]. Nurses' average score is also found weak in the studies conducted in USA, Australia, Hong Kong, and Egypt [9,11,18,21,22]. This difference might be attributed to study topics, setting and regional conditions, the type of hospital, and the way to develop and implement educational programs in relation to disaster preparedness.…”
Section: Discussionmentioning
confidence: 81%
“…The study by Ghanbari et al showed that 80.7% of nurses are not trained for such situations [6]. The studies in Hong Kong [11], Jordan [4], Singapore [12], and Egypt [9] have also reported nurses' insufficient preparedness in disasters. Dolatabadi et al mentioned insufficient knowledge and unpreparedness as the causes of emotional stresses meddling with nurses' tasks in such situations; they believed that nurses' preparedness for responding in disasters helped them to boost their confidence, and reduce the loses and vulnerabilities in confronting with unpredictable incidents [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that most nurses are not ready to respond to mass casualties and training and skills are not at sufficient level to make the appropriate initiative (Fothergill et al, 2005;Fung et al, 2008;Al Khalaileh et al, 2012;Diab & Mabrouk, 2015;Seyedin et al, 2015;Labrague et al, 2016).…”
Section: Nurses' Status Of Disaster Preparednessmentioning
confidence: 99%